Dmitrij Klenovskij. Geheimnis des Seins. Gedichte zu Tod, Transzendenz und dem Schutzengel - Kasack, Wolfgang (Arbeiten und Texte zur Slavistik, 2002)
The first monograph on the Russian lyric poet Dimitrij Klenovskij (1892-1976) is presented here. He is one of the few who remained in Germany after fleeing from the Soviet Union in World War II until his death. Important Russian poets such as Anna Achmatova and Ivan Bunin counted him among the best Russian poets, Gleb Struve and Johannes von Gunther paid him a high esteem as a literary scholar, but in the Slavic literature he was hardly noticed as an emigrant. His poetry is in many ways in search of the "mystery of being" and, through its main themes examined here - his life with death and with the spiritual helpers, the angels - penetrate into depths that are essential for the recognition of man's existence beitragen.dern